2021
DOI: 10.1186/s10086-021-01998-0
|View full text |Cite
|
Sign up to set email alerts
|

The mechanical properties and thermal conductivity of bamboo with freeze–thaw treatment

Abstract: The aim of this research was to investigate the effect of freeze–thaw treatment on bamboo with different initial moisture content (water-saturated, air-dried and oven-dried). Bamboo (Phyllostachys pubescens) were treated with two freeze treatments and its microstructure, chemical composition, mechanical properties and thermal conductivity were characterized by field emission scanning electron microscopy (FE-SEM), Fourier-transform infrared spectroscopy (FT-IR), X-ray diffraction (XRD), mechanical testing machi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The continuous photolysis of lignin and the decrease in mechanical strength caused a constant decrease in E′. The peak near T g shifted toward higher temperatures in E″, which was also caused by a decrease in lignin and a relative increase in the cellulose content with a higher primary transition temperature than lignin [ 45 ]. Similarly, in tan δ , the primary transition peak was consistent with E″, and the secondary transition peak gradually decreased in height.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The continuous photolysis of lignin and the decrease in mechanical strength caused a constant decrease in E′. The peak near T g shifted toward higher temperatures in E″, which was also caused by a decrease in lignin and a relative increase in the cellulose content with a higher primary transition temperature than lignin [ 45 ]. Similarly, in tan δ , the primary transition peak was consistent with E″, and the secondary transition peak gradually decreased in height.…”
Section: Resultsmentioning
confidence: 99%
“…Freeze–thaw cycle and damp–heat treatment resulted in the peak intensity at 3400 cm −1 being slightly lower, which was attributed to the two free hydroxyl groups in the cellulose amorphous region combined at a high temperature and the formation of hydrogen bonds by the action of water molecules. In addition, the peak intensity at 2900 cm −1 and 1060 cm −1 reduced, owing to the decomposition of aliphatic, β-glycoside structure and other substances [ 26 , 45 ]. Degradation of lignin was manifested in a decrease in the peak at 1640 cm −1 and 1260 cm −1 , which was attributed to the benzene ring skeleton vibration [ 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Wang et al reported that freeze–thawing pretreatment effectively shortened the vacuum freeze-drying duration by 4–6 h and reduced energy consumption by 10.0–15.1 g/100 g compared with the traditional alkaline-dewaxing method. During the freeze–thaw treatment, ice crystals are pierced into the cell wall, causing water to be better able to exit the plant body since the ice crystals pierce the cell wall. , Dhiman et al described blanching as the result of solubilization of pectic polymers that play an important role in cell–cell adhesion, as well as depolymerization of these polymers.…”
Section: Introductionmentioning
confidence: 99%
“…During the freeze–thaw treatment, ice crystals are pierced into the cell wall, causing water to be better able to exit the plant body since the ice crystals pierce the cell wall. 18 , 19 Dhiman et al 20 described blanching as the result of solubilization of pectic polymers that play an important role in cell–cell adhesion, as well as depolymerization of these polymers.…”
Section: Introductionmentioning
confidence: 99%
“…For the last few years, bio-inspired superhydrophobic surfaces have attracted more attention in industrial and research applications [1]. As a green, renewable, inexpensive, easily harvested, biodegradable, and abundant resource, balsa wood has great potential for the development of multi-functional composite materials because of its unique chemical components and natural hierarchical porous structure [2], which can be achieved by exploiting the unique chemical components, high porosity, and natural hierarchical structure of wood in one step. In past decades, wood has been functionalized as a template with multiple functions and applications, such as for lightweight structural materials, transparent windows, oil-water separation, water processing, solar evaporation, and other functions.…”
Section: Introductionmentioning
confidence: 99%